Exploring Reliability and Validity of the Deployment Risk and Resilience Inventory‐2 Among a Nonclinical Sample of Discharged Soldiers Following Mandatory Military Service. Issue 6 (17th November 2016) - Maoz, Hagai; Goldwin, Yiftach; Lewis, Yael Doreen; Bloch, Yuval
Abstract: The Deployment Risk and Resilience Inventory (DRRI) is a widely used questionnaire assessing deployment‐related risk and resilience factors among war veterans. Its successor, the DRRI‐2, has only been validated and used among veterans deployed for overseas military missions, but because many countries still enforce compulsory military service, validating it among nonclinical samples of healthy discharged soldiers following mandatory service is also a necessity. In the current study, a sample of 101 discharged Israeli soldiers (39 males, 62 females; mean time since discharge 13.92, SD = 9.09 years) completed the DRRI‐2. There were 52 participants who completed the questionnaire at a second time point (mean time between assessments 19.02, SD = 6.21 days). Both physical and mental health status were examined, as well as symptomatology of depression, anxiety, and posttraumatic stress disorder. Cronbach's αs for all latent variables in the inventory ranged from .47 to .95. The DRRI‐2 risk factors were negatively associated with psychological functioning, whereas resilience factors were positively associated with better self‐reported mental health. Test‐retest reliability coefficients were generally high (Pearson correlations were .61 to .94, all p values < .01). Our study provides evidence for the reliability and validity of the DRRI‐2 in assessing salient deployment experiences among a nonclinical sample following mandatory military service.